Validated spectrofluorimetric method for the determination of atorvastatin in pharmaceutical preparations - Mohie M.K. Sharaf El-Din; Fathy M.M. Salama; Mohamed W.I. Nassar; Khalid A.M. Attia; Mohamed M.Y. Kaddah (Elsevier, 2012)
A rapid, sensitive and simple spectrofluorimetric method was developed for the estimation of atorvastatin. In this method, the native fluorescence characteristics of atorvastatin have been studied in both acidic and basic media. High sensitivity was obtained with 5% acetic acid at 389Â nm using 276Â nm for excitation. Regression analysis showed a good correlation coefficient (r=0.9995) between fluorescence intensity and concentration over the range of 1.5â4Â Î¼g/mL with detection limit of 0.012Â Î¼g/mL. The proposed method was successfully applied to the analysis of atorvastatin in pure and pharmaceutical dosage forms with average recovery of 100.29Â±0.47%. The results were compared favorably with those of the reported method. Keywords: Spectrofluorimetric, Atorvastatin, Native fluorescence